"Choice, welfare and measurement" - "Sen, Amartya" (Delhi, 2002)
Nobel Prize-winning economist Amartya Sen has been a distinguished and influential scholar in development economics for over twenty years, and this edited volume seeks to reflect his interests and the inspiration he has provided for others. The editors have succeeded in creating a coherent and stimulating set of papers from well-known contributors. The volume deals with the enduring themes of Amartya Sen's work, ranging through theoretical issues of development economics to the philosophical foundation of welfare systems, and ethics in society. This work will be of special interest to academics specializing in development and welfare economics, and those with an interest in ethics and the philosophy of economics. Contributors: Anthony B. Atkinson, Pranab Bardhan, Jeffrey L. Coles, Rajat Deb, Jean Dreze, Louis Gevers, Peter J. Hammond, Ravi Kanbur, Eric S. Maskin, Robert Nozick, Siddiq Osmani, Martin Ravallion, Kevin Roberts, Mrinalini Saran, Robert Solow, and Serve Wilbaut.
Keywords: Welfare economics